ANALISIS PERTIMBANGAN HAKIM MAHKAMAH AGUNG DALAM MEMBATALKAN PUTUSAN BANDING CLASS ACTION (STUDI PUTUSAN NOMOR 896 K/PDT/2019) - Rafli Abigail Wijanarko; Ismawati Septiningsih (Sebelas Maret University, 2025)
This article analyzes the legal considerations of the Supreme Court judges in Decision Number 896 K/Pdt/2019 in overturning the DKI Jakarta High Court Decision Number 192/Pdt/2018/PT.DKI. The Supreme Court judge has a different opinion from the decision of the DKI Jakarta High Court on the case of normalization of the Ciliwung Riverbank involving the Bukit Duri village community and the Central Jakarta government, in this case the Head of the Ciliwung Cisadane River Basin Center (BBWSCC). Based on the results of the discussion, it shows that the Supreme Court judge in his consideration emphasized on the non-fulfillment of the notification and option-out provisions which resulted in formal legal errors. In addition, the Supreme Court judge considered that the validity of a class action lawsuit if it is stated in a court decision. In the absence of a determination issued by the Judex Factie, the case did not meet the criteria as a class action.